2013
DOI: 10.1007/s10902-013-9428-9
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Well-Being in School-Based Mentoring Through Basic Psychological Needs Support: Does It Really Count?

Abstract: The main goal of this research was to assess whether satisfying basic psychological needs (BPN) in a Portuguese school-based mentoring (SBM) program improved the mentored students' well-being. One uncommon feature of this program was that the mentors were also teachers of the mentees. A two-wave experimental study design was implemented to compare the mentored (n = 157) and non-mentored students (n = 160). Surveys were completed twice, with a 6-month interval between time points 1 and 2. The results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Perceptions of school environment were the only difference between the groups reaching statistical significance. Additionally, results indicated that gains on all dependent measures of wellbeing were more positive among mentees perceiving increased satisfaction of their needs compared to mentees in the opposite condition [30].This study demonstrates the capacity for mentoring programs to increase basic psychological need satisfaction among mentees when mentors are trained in techniques known to promote each need. This study also highlights the need for mentors to adopt a more balanced approached while supporting their mentees needs.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Perceptions of school environment were the only difference between the groups reaching statistical significance. Additionally, results indicated that gains on all dependent measures of wellbeing were more positive among mentees perceiving increased satisfaction of their needs compared to mentees in the opposite condition [30].This study demonstrates the capacity for mentoring programs to increase basic psychological need satisfaction among mentees when mentors are trained in techniques known to promote each need. This study also highlights the need for mentors to adopt a more balanced approached while supporting their mentees needs.…”
mentioning
confidence: 66%
“…Mentoring took place during weekly one-on-one sessions outside of regular class time and was augmented with weekly 90-minute group sessions. During group sessions, mentor-mentee pairs collaboratively discussed issues surrounding school, social integration, and other relevant themes.Results indicated that pre-post test variations for three of the dependent variables (hope, school environment, and perceived competence in learning) were significantly correlated with basic psychological need satisfaction among mentees [30]. Further, while comparing students who reported increased need satisfaction in both the mentored and non-mentored groups, results revealed that mentored students exhibited higher ratings for school environment, physical well-being, and perceived competence in learning compared to their non-mentored counterparts [30].…”
mentioning
confidence: 85%
See 3 more Smart Citations